2004
DOI: 10.1242/dev.01241
|View full text |Cite
|
Sign up to set email alerts
|

Selective loss of imprinting in the placenta following preimplantation development in culture

Abstract: Preimplantation development is a period of dynamic epigenetic change that begins with remodeling of egg and sperm genomes, and ends with implantation. During this time, parental-specific imprinting marks are maintained to direct appropriate imprinted gene expression. We previously demonstrated that H19 imprinting could be lost during preimplantation development under certain culture conditions. To define the lability of genomic imprints during this dynamic period and to determine whether loss of imprinting con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
310
2
6

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 403 publications
(354 citation statements)
references
References 49 publications
36
310
2
6
Order By: Relevance
“…In this study, the in vivo-produced blastocysts were different from the other blastocysts in that there was no time in culture. For example, previous studies have shown that epigenetic changes caused by in vitro preimplantation culture results in aberrant methylation and expression of a number of imprinted genes (Sasaki et al, 1995;Doherty et al, 2000;Mann et al, 2004). Further, the authors suggest that the epigenetic remodeling and reprogramming of the trophoblast may be more sensitive to the disruptive effect of the culture media than the ICM.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the in vivo-produced blastocysts were different from the other blastocysts in that there was no time in culture. For example, previous studies have shown that epigenetic changes caused by in vitro preimplantation culture results in aberrant methylation and expression of a number of imprinted genes (Sasaki et al, 1995;Doherty et al, 2000;Mann et al, 2004). Further, the authors suggest that the epigenetic remodeling and reprogramming of the trophoblast may be more sensitive to the disruptive effect of the culture media than the ICM.…”
Section: Discussionmentioning
confidence: 99%
“…In case of the BiCHMs, the labile nature of maternal imprints in placental tissues during early development may explain the loss of maternal imprints. 22 Finally, the abnormal methylation patterns on the maternal alleles of maternally or paternally expressed genes in biparental molar tissues may have not occurred at all DMRs at the same time, but resulted from several events that altogether led to the molar phenotype. …”
Section: Discussionmentioning
confidence: 99%
“…First, in vitro culture may impinge on the imprinting process of IVF blastocysts. This hypothesis is supported by recent evidence that murine H19 imprinting is lost in embryos following culture in Whitten's medium and that this loss of imprinting persists in mid-gestation conceptuses (Doherty et al 2000;Mann et al 2004). However, the fact that approximately 60% of IVF blastocysts, when compared with in vivo embryo transfers, result in live births suggests that the effects of in vitro culture may not explain fully the results obtained (Peterson and Lee 2003).…”
Section: Genomic Imprinting Statusmentioning
confidence: 93%